Development and Evaluation of Salbutamol Sulphate Loaded Ethyl Cellulose Microcapsules using Emulsion Solvent Evaporation Technique - Alam, Md Shamsul; Chowdhury, Jakir Ahmed; Sadat, Sams Mohammad Anowar; Reza, Md Selim (Bangladesh Pharmaceutical Journal, 2015)
Ethyl cellulose (EC) microcapsules containing Salbutamol sulphate (SS) were prepared through emulsion-solvent evaporation technique. Microcapsules were compressed and in-vitro release profiles were studied from both microcapsules and their compressed matrix tablets. Different amounts of drug were added in order to obtain various drugs to polymer ratios and it was found that the size of microcapsules reduced with the increase in core loading. In the preparation of formulations, Tween 80 was used as an emulsifying or dispersing agent and light liquid paraffin (LLP) was used as oil phase. The in-vitro release of EC microcapsules was studied in distilled water at 37º ± 0.5°C. A biphasic release behavior of SS from microcapsules was observed. In case of microcapsules, an immediate release was observed but for their compressed tablet form, initially a burst effect and then slow release were observed which was extended for 8 hours. In order to further investigate the type of drug release mechanism, the dissolution data were plotted according to the different kinetic models. In-vitro dissolution studies showed that zero-order and square-root of time (Higuchi model) release characteristics were exhibited. Bangladesh Pharmaceutical Journal 18(2): 132-136, 2015